KEPERCAYAAN, WORD OF MOUTH DAN KELENGKAPAN PRODUK UNTUK MENDORONG KEPUASAN PELANGGAN PADA TOKO TYAS LESTARI DI SURABAYA - Dimas Tyas; Endah Budiarti (Nirta Learning Centre, 2025)
The food packaging industry in Surabaya is marked by intense competition, necessitating effective marketing strategies to enhance customer satisfaction. This study focuses on the influence of trust, Word of Mouth, and product completeness on customer satisfaction at Toko Tyas Lestari in Surabaya. These three variables were selected due to their theoretical and practical relevance in maintaining sales stability and fostering customer loyalty. Amid fluctuating sales, the research aims to determine the extent to which these factors affect customer satisfaction, both individually and collectively. A quantitative research method with a survey approach was employed, involving 100 respondents. Data were collected using a structured questionnaire based on a Likert scale. The analysis was conducted using multiple linear regression to examine both individual and collective impacts, alongside validity and reliability tests to ensure the instrument’s consistency. The study was conducted at Toko Tyas Lestari, a well-known provider of food packaging products in Surabaya, recognized for its comprehensive product range. The findings reveal that trust and product completeness have a significant positive influence on customer satisfaction. In contrast, Word of Mouth does not significantly impact customer satisfaction. Collectively, the three variables contribute to improving customer satisfaction, although WOM does not make a significant individual contribution. These results imply that Toko Tyas Lestari should prioritize enhancing trust and product completeness to retain customer loyalty while continuing to manage WOM as a supportive factor. Keywords: Trust, Word of Mouth, Product Completeness, Customer Satisfaction, Toko Tyas Lestari.